IMPLEMENTATION AND DEVELOPMENT OF THE CORPORATE MANAGEMENT SYSTEM IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2023)
This article analyzes the implementation of a corporate governance system in joint-stock companies and limited liability companiesof Uzbekistan, an analysis of current corporate governance in accordance with global principles of corporate governance and diversification of the national corporate governance system in the context of economic diversification, as well as the development of recommendations and proposals on corporate governance in activities of joint stock companies.